Adjusting the structure combinations of plant communities in urban greenspace reduced the maintenance energy consumption and GHG emissions - Liu, Yang; Yang, Qiusheng; Duan, Lichao (Journal of Environmental Engineering and Landscape Management, 2018)
Maintaining urban greenspace results in energy use and GHG emissions. To understand the change of the annual maintenance energy consumption and GHG emissions in varying combinations of plant structures (plant density or proportion of area covered) in urban greenspace, this study investigated 34 urban plant communities as sample plots (20×20 m), and divided them into woodland, shrub, herbaceous and grassland layers. The average energy use and GHG emissions in the woodland layer were 18.64 MJ/tree/y–1 and 0.23 kg/CO2-e/tree/y–1, respectively. In the shrub, herbaceous, and grassland layers, the average energy consumption was 3.73, 2.27, 7.23 MJ/m2/y–1, and the average GHG emissions were 0.06, 0.02, 0.09 kg/CO2-e/m2/y–1, respectively. The energy use and GHG emission curves had parabolic trends as the plant density in the woodland layer increased and increasing curves with two peaks as the plant area proportions of the shrub, herbaceous, and grassland layers increased. The annual maintenance of urban greenspace can divide into low, average and high levels of energy consumption and GHG emissions due to the change in the plant structure combinations. Furthermore, city managers and landscape designers can refer to the energy consumption and GHG emissions trends to understand the environmental impact of maintenance tasks. The future plant structures in greenspace can be better designed to improve ecosystem services based on limiting the maintenance environmental impacts.